The Effectiveness of Fire Safety Education in Enhancing the Knowledge of SMAN 1 Gebog Students - Syafina Alma Farika; Muhammad Navis Mirza; Charisa Mahda Kumala; Nabila Hikmatul Azka; Ashfanul Muna; Siti Rohmatin Nafisah; Ali Sofi’i; Tia Nely Agustin; Achmad Faisol Muith (Yayasan Adra Karima Hubbi, 2024)
Fire safety is crucial in protecting lives and property. This study aims to evaluate the effectiveness of fire safety education in enhancing the knowledge of students at SMAN 1 Gebog. The introduction explains that schools are potential environments for fires, necessitating interventions to enhance awareness and preparedness. The research employed a quasi-experimental design with pretest-posttest on 40 eleventh-grade students, who received education through presentations and simulations over 2 hours. The analysis showed a significant increase in students' knowledge after the intervention, with the average pretest score of 5.5 rising to 9.0 in the posttest. Statistical tests (t-test) confirmed that this improvement was statistically significant (t = 12.41, p < 0.001). The study concludes that the education was effective in enhancing students' knowledge of fire safety in schools. To ensure sustainability, it is recommended to develop training for teachers as trainers in the future, thereby enabling the program to continue and sustainably mitigate fire risks in school environments.